A CLASSROOM EXPERIENCE: THE POWER OF WILL, DILIGENCE AND TRY DURING THE COVID-19 PANDEMIC - HIKMAH, HIKMAH (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Mastering English seems very difficult for some people because the perception of English as a foreign language has fossilized in their mind. People’s opinion about English as an “elite language” that can be learned by certain people make it more complicated. Language is habit; those who do not have basic of English can master it better than people who study English. People, who have high motivation, will and diligence can be success, as they will keep trying to get it. This article observed during the pandemic era about the ability of a learner who is from non English Department, but can speak English well. He can prove that people speak English are not always influenced by their mother tongue. He is considered as one of successful students in his college because of his effort. The urgency of this research regarding to learning English strategy through the power of will, diligence and try during the covid-19 era. The data was collected through an interview. Based on the interview, it is concluded that although English is not major subject, it does not mean students can not speak English well. The power of will, diligence and try prove it.